2019
DOI: 10.3390/catal9121003
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Lycopene Production in Escherichia coli by Expression of Two MEP Pathway Enzymes from Vibrio sp. Dhg

Abstract: Microbial production is a promising method that can overcome major limitations in conventional methods of lycopene production, such as low yields and variations in product quality. Significant efforts have been made to improve lycopene production by engineering either the 2-C-methyl-d-erythritol 4-phosphate (MEP) pathway or mevalonate (MVA) pathway in microorganisms. To further improve lycopene production, it is critical to utilize metabolic enzymes with high specific activities. Two enzymes, 1-deoxy-d-xylulos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…In addition, Lycopene is a carotenoid referring to C40 terpenoids and is broadly found in various plants, particularly vegetables and fruits. It has been shown that MVA and MEP-pathways directly influence the biosynthesis production of Lycopene (Kim et al, 2019; Wei et al, 2018). While Wille et al (2004) showed that β-carotene and Lutein are synthesized using intermediates from the MEP pathway, Opitz et al (2014) revealed that both MVA and MPE pathways contribute to producing isoprenoids such as β-carotene and Lutein.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Lycopene is a carotenoid referring to C40 terpenoids and is broadly found in various plants, particularly vegetables and fruits. It has been shown that MVA and MEP-pathways directly influence the biosynthesis production of Lycopene (Kim et al, 2019; Wei et al, 2018). While Wille et al (2004) showed that β-carotene and Lutein are synthesized using intermediates from the MEP pathway, Opitz et al (2014) revealed that both MVA and MPE pathways contribute to producing isoprenoids such as β-carotene and Lutein.…”
Section: Resultsmentioning
confidence: 99%
“…SP1, three heterologous genes ( crtE encoding geranylgeranyl diphosphate (GGPP) synthase, crtB encoding phytoene synthase and crtI encoding phytoene desaturase) from Lamprocystis purpurea were introduced for lycopene production, and additional crtY gene encoding lycopene cyclase from Pantoea ananatis was introduced for β -carotene production. For the plasmid of lycopene production, p1EBI plasmid which encodes crtE-crtB-crtI gene under same P tac promoter in a polycistronic manner was used [23] . To prepare β -carotene plasmid, p1EBIY, vector fragment was amplified using the primers of crtY_v-F and crtY_v-R with p1EBI as a template.…”
Section: Methodsmentioning
confidence: 99%
“…dhg [22] was characterized to utilize alginate and produce diverse high-value added products, while exhibiting fast growing profile and engineering potential. Further investigation revealed that enzymes mediating the methylerythritol-4-phosphate (MEP) pathway found in the strain exhibits better activity than those of E. coli , implying Vibrio species could be an promising workhorse when producing isoprenoid or carotenoid metabolites [23] . Likewise, the accumulation of microbial and genetic resources is expected to enrich the realm of genetic compartments regarding metabolic engineering of Vibrio species for the production of value-added products.…”
Section: Introductionmentioning
confidence: 99%
“…Many challenges in retinal production have been addressed using metabolically engineered E. coli cells. Several aspects have been considered for the efficient production of carotenoid, which can be used as a substrate for BCOs, from glucose or glycerol via the endogenous MEP pathway and exogenous MVA pathway in metabolically engineered cells [63][64][65][66][67][68]. However, studies on the engineering of BCOs, which are crucial enzymes for catalyzing the last step of the retinal biosynthetic pathway, are still lacking.…”
Section: Future Perspectives Of Bco In Synthetic Bacteriamentioning
confidence: 99%